2006
DOI: 10.1111/j.1365-2958.2006.05248.x
|View full text |Cite
|
Sign up to set email alerts
|

RA domain‐mediated interaction of Cdc35 with Ras1 is essential for increasing cellular cAMP level for Candida albicans hyphal development

Abstract: SummaryMany Ras GTPases activate their effectors through binding at a conserved Ras association (RA) domain. An example is the activation of the budding yeast adenylate cyclase Cyr1 by Ras1 and Ras2. Candida albicans Ras1 is speculated to similarly activate Cdc35, the orthologue of Cyr1, for hyphal development. Here, we have investigated whether the RA domain mediates Ras1-Cdc35 interaction and how this interaction regulates cAMP levels and morphogenesis. Yeast two-hybrid assays suggested that Ras1 interacts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(101 citation statements)
references
References 66 publications
3
96
1
1
Order By: Relevance
“…Both phenotypes are shared with mutants lacking the guanine nucleotide exchange factor Cdc25 (193), suggesting that the Cdc25-Ras1 pathway functions upstream of the cAMP-PKA pathway. This is supported by a recent study in which a clear interaction between Ras1 and adenylate cyclase, Cyr1, is demonstrated (90). However, as with the situation in S. cerevisiae, Ras1 also appears to function upstream of the Cek1 MAPK pathway ( Fig.…”
Section: Camp-pka Pathwaysupporting
confidence: 59%
“…Both phenotypes are shared with mutants lacking the guanine nucleotide exchange factor Cdc25 (193), suggesting that the Cdc25-Ras1 pathway functions upstream of the cAMP-PKA pathway. This is supported by a recent study in which a clear interaction between Ras1 and adenylate cyclase, Cyr1, is demonstrated (90). However, as with the situation in S. cerevisiae, Ras1 also appears to function upstream of the Cek1 MAPK pathway ( Fig.…”
Section: Camp-pka Pathwaysupporting
confidence: 59%
“…Ras1 and Gpa2 both function upstream of the adenylyl cyclase Cyr1, and the physical interaction between Ras1 and Cyr1 is essential for increasing cellular cAMP levels (173,490). Cyr1 is the single adenylyl cyclase in C. albicans and therefore is the sole source of cAMP production in the cell.…”
Section: Major Morphogenetic Signaling Cascadesmentioning
confidence: 99%
“…The cAMP-protein kinase A-pathway plays a central role in the induction of hyphae: the adenylate cyclase Cyr1p is activated by a number of stimuli, such as CO 2 -concentration, and signals from other proteins, e.g. the small G-protein Ras1p and the cytoskeleton (Fang and Wang, 2006;Klengel et al, 2005;Rocha et al, 2001;Zou et al, 2010). Ras1p itself is activated in response to multiple signals, like nitrogen shortage or the presence of serum (Biswas and Morschhäuser, 2005;Feng et al, 1999).…”
Section: Introductionmentioning
confidence: 99%